Wątki staroegipskie w powieściach Agathy Christie = Old egyptian motifs in Agatha Christie's fiction - Popielska-Grzybowska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the paper shows what ancient Egyptian motifs Agatha Christie used in her detectivestories. Moreover, she explains what means of expression and plot devices the mistress of crime stories used to create the historical background of her novels. Agatha Christie mentions her fascination with the work of archaeologists in her autobiography. Her passion for archaeology was caused, most probably, by the fact that her second husband, Max Mallowan, was a worldwide known archaeologist, who conducted excavations in the Near East. Thus, in many of her novels there are references to ancient times and ancient monuments. Moreover, the plot of one of Christie's novels, "Murder in Mesopotamia", is set at the excavation site.
Keywords: Christie, Agatha (1890-1976); powieść kryminalna; literatura angielska; 20 w.